COVID‐19 vaccine hesitancy: The synergistic effect of anxiety and proactive coping - MacKenzie L. Hughes; Shevaun D. Neupert; Emily L. Smith; Clara W. Coblenz; Samuel G. Macy; Ann Pearman (Wiley, 2023)
Abstract Background This study sought to identify cognitive and behavioral predictors of COVID‐19 vaccine hesitancy. Specifically, this study examined the effect of anxiety about developing COVID‐19 and proactive coping behavior on the likelihood of reporting COVID‐19 vaccine hesitancy in a sample of adults living in the United States. Methods An online survey of proactive coping strategies, anxiety related to developing COVID‐19, and vaccine hesitancy was administered in October 2020 to 534 adults aged 21-79‐years old. Age, gender, race, self‐rated health, years of education, COVID‐19 knowledge, and perceived constraints were included as covariates. Results Over half of the study participants (56.7%) were COVID‐19 vaccine hesitant. People who were less anxious about developing COVID‐19 were more likely to be vaccine hesitant. A statistically significant COVID‐19 anxiety × proactive coping interaction showed the odds of vaccine hesitancy was highest among individuals with low anxiety about developing COVID‐19 and high proactive coping, whereas vaccine hesitancy was lowest among individuals with high COVID‐19 anxiety and high proactive coping. Conclusion Results support a future‐oriented approach to public health outreach efforts regarding COVID‐19 vaccines. Improvement of proactive coping skills and emphasis on the likelihood of contracting COVID‐19 may be more effective in increasing vaccine uptake than simply restating scientific facts regarding safety or efficacy.